2011
DOI: 10.1097/sap.0b013e318209a744
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Course of the Extensor Pollicis Longus

Abstract: The extensor pollicis longus (EPL) is a consistent structure with rare anomalies, the most common being a group of different tendon duplications passing through the fourth compartment without symptoms. The second form comprises anomalies in the course of the EPL having significant clinical importance due to the predisposition for creating tenosynovitis of the EPL mimicking other types of tendon tenosynovitis. Clinical symptoms of radial dorsal wrist pain mimicking intersection syndrome or de-Quervain disease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Anomalous course of the EPL passes through other compartment out of the 3rd compartment. Anomalous course of the EPL is known to be much rare than duplication, as much as 5 cases were reported previously [6]. In our case, the EPL passes wrist though the 3rd compartment, but it is out of the 3rd compartment at the carpal bone level and inserted on the radial side of the thumb as the 1st compartment.…”
Section: Discussionsupporting
confidence: 47%
“…Anomalous course of the EPL passes through other compartment out of the 3rd compartment. Anomalous course of the EPL is known to be much rare than duplication, as much as 5 cases were reported previously [6]. In our case, the EPL passes wrist though the 3rd compartment, but it is out of the 3rd compartment at the carpal bone level and inserted on the radial side of the thumb as the 1st compartment.…”
Section: Discussionsupporting
confidence: 47%
“…Indeed, a variant course of a single EPL tendon outside of the third compartment is extremely rare and only four reports [1,[4][5][6] were found in the English literature. These four reports mostly describe passage of the EPL radial to Lister's tubercle and within the first compartment.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Abe et al [1] described two cases of single EPL tendon running radial to Lister's tubercle into the fist extensor compartment. Also, Rubin et al [5] reported a single EPL tendon in the first compartment with initial symptoms resembling intersection syndrome, but the condition was subsequently diagnosed as de Quervain's disease. These two sets of authors report the absence of the snuff box and the absence of typical EPL skin contours due to EPL anomaly.…”
Section: Discussionmentioning
confidence: 97%
“…To date only 5 cases of anomalous course of EPL tendon in symptomatic patients have been reported in the English literature. [ 6 8 , 12 ] Nishijo et al [ 6 ] described duplicated EPL passing radial to Lister's tubercle into the first dorsal compartment and in her left hand, ulnar to Lister's tubercle in a normal course. Sawaizumi et al [ 12 ] also described the anomalous course of duplicated EPL tendon, one of them in a new compartment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 , 4 , 5 ] However, it is a rare condition that presents clinical symptoms very similar to de Quervain's disease due to the anomalous course and tenosynovitis of extensor pollicis longus (EPL) tendon despite few published reports. [ 6 , 7 , 8 ]…”
Section: Introductionmentioning
confidence: 99%